2018
DOI: 10.1098/rsos.172357
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between polymorphisms in cell-cycle genes and environmental factors in regulating cholinesterase activity in people with exposure to omethoate

Abstract: Cholinesterase activity (ChA), the effective biomarker for organophosphate pesticide exposure, is possibly affected by single nucleotide polymorphisms (SNPs) in cell-cycle-related genes. One hundred and eighty workers with long-term exposure to omethoate and 115 healthy controls were recruited to explore the gene–gene and gene–environment interactions. The acetylthiocholine and dithio-bis-(nitrobenzoic acid) method was used to detect the cholinesterase activities in whole blood, erythrocytes and plasma. Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Up to date, there were no studies to investigate the association of interaction among the SNPs of P53 , P21 , MDM‐2 , and MMP‐9 with ND or functional outcome after IS. However, Duan et al (2018) has revealed that interaction among P53 , P21 , and MDM‐2 may affect cholinesterase activity in people with exposure to omethoate. Thus, we reason that the high‐risk interaction among P53 , MDM‐2 , and MMP‐9 could synergistically activate the intrinsic apoptotic pathway and ischemia‐induced apoptotic cell death, thereby increasing the risk of ND and poor functional outcome after IS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Up to date, there were no studies to investigate the association of interaction among the SNPs of P53 , P21 , MDM‐2 , and MMP‐9 with ND or functional outcome after IS. However, Duan et al (2018) has revealed that interaction among P53 , P21 , and MDM‐2 may affect cholinesterase activity in people with exposure to omethoate. Thus, we reason that the high‐risk interaction among P53 , MDM‐2 , and MMP‐9 could synergistically activate the intrinsic apoptotic pathway and ischemia‐induced apoptotic cell death, thereby increasing the risk of ND and poor functional outcome after IS.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed information of the 9 SNPs in this study was summarized in Table 7. Extensive evidences have shown that SNPs of P53 and MDM2 rs2279744 play important roles in DNA damage and cell apoptosis and were independently related to high risk of cancer (Chen et al, 2015; Duan et al, 2018; Liu et al, 2011). Human P 53 Arg72Pro (rs1042522) SNP controls susceptibility to ischemia‐induced neuronal apoptosis and the functional outcome after stroke (Gomez‐Sanchez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations